2018
DOI: 10.4103/ijpsym.ijpsym_109_18
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study on Empathy and its Correlates: A Cross-sectional Assessment among Medical Students of a Government Medical College of India

Abstract: Background: Empathy is a desirable quality in every clinician. It is a crucial determinant of patient–physician communication and relation. There are very few existent Indian studies on empathy of medical students and its correlates. Aim: The aim of the study was to assess empathy level of medical students and its correlates. Methodology: It was a cross-sectional, hospital-based, analytical observational study conducted from July to November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
7
12
5
Order By: Relevance
“…The mean RF score in our study sample was 4.49 (SD = 1.86), corresponding to a slightly below normal RF score (ordinary RF score = 5). This finding is consistent with previous studies supporting evidence for the decline of medical students' empathy during training [50][51][52][53][54]. Physicians with a higher degree of empathy are even more prone to emotional fatigue [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean RF score in our study sample was 4.49 (SD = 1.86), corresponding to a slightly below normal RF score (ordinary RF score = 5). This finding is consistent with previous studies supporting evidence for the decline of medical students' empathy during training [50][51][52][53][54]. Physicians with a higher degree of empathy are even more prone to emotional fatigue [25].…”
Section: Discussionsupporting
confidence: 92%
“…Although mentalizing has been shown to be relatively stable, contextual factors are known to have an influence, such that increasing arousal and stress may lead to fluctuations [15]. Previous research has indicated that external factors impact on mentalizing abilities, where stress and negative stress perception have a negative impact on empathy, whereas social support and career satisfaction were found to have a beneficial effect on empathy measures [50,57]. Empathy is not correlated with personality traits [51].…”
Section: Discussionmentioning
confidence: 98%
“…This is quite close to the findings of Biswas et al who, in a similar study on medical students, reported a mean empathy score of 98.5±12.5 with a maximum and minimum score obtained as 129 and 67 respectively. 10 It is also similar to the findings of another study by Chatterjee et al who reported a mean empathy score of 96.01±14.56 with a maximum score of 140 and Shashikumar et al who reported a mean empathy score of 102.9. 11,12 However, our findings were quite low as compared to many Western studies conducted by Santos ) and much higher than those reported by Tariq et al in their study which was a mere 4.77±0.72.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to the findings of Biswas et al who in their study found a statistically significant difference (p<0.05) between the higher mean empathy scores of female medical students (100.7±12.9) as compared to male students (96.9±12.0). 10 Papageorgiou et al too reported that there was a tendency for female students to have higher empathy scores compared to male students. 18 This is also in agreement with the findings of Chatterjee et al who in their study reported a highly significant statistical difference (p<0.01) between the higher mean empathy scores of female students (102.21±13.30) as compared to male students (94.38±14.45).…”
Section: Discussionmentioning
confidence: 99%
“…Empathy in patient care was defined by Hojat et al [1] as a predominantly cognitive characteristic that involves not only an understanding of patients' experiences, concerns, and perspectives but also a capacity to communicate this understanding to patients and an intention to help them. Based on a comprehensive review of relevant literature, it is evident that empathy plays an essential role in achieving optimal outcomes in medical care by optimizing careful history taking, diagnostic accuracy, compliance to treatment, and maximum utilization of resources, thereby increasing patients' satisfaction and quality of health care [2][3][4]. As such, it would be fruitful for medical school faculty to promote the cultivation of empathy among medical students as part of the contemporary "professionalism" system in medicine [5].…”
Section: Introductionmentioning
confidence: 99%